2007
DOI: 10.3398/1527-0904(2007)67[161:zpafco]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Zoogeographic Patterns and Faunal Change of South Dakota Fishes

Abstract: We summarized historic and recent fish distributions in South Dakota and analyzed fish faunal similarity at 2 spatial scales (geomorphic province and river drainage) for both historic (native) and recent (post-1990) faunas. We quantified zoogeographic patterns between geomorphic provinces and among neighboring river drainages for historic and recent faunas. We also quantified faunal change (species losses and additions) between provinces and among drainages. Ninety-seven fishes were native to South Dakota, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…While the proportion of non-native species increased significantly between the surveys, it was extremely low in both. Much previous research into different types of BH has focused on invasion by non-native species as a principal cause (Castro et al 2007;Hoagstrom et al 2007;McKinney & La Sorte 2007;Magee et al 2008). While non-native species can cause large losses of native species in some circumstances (Maskell et al 2006a), national surveys accord with the results of this study in showing that non-natives are minor components of many British plant communities (Maskell et al 2006b).…”
Section: Discussionsupporting
confidence: 76%
“…While the proportion of non-native species increased significantly between the surveys, it was extremely low in both. Much previous research into different types of BH has focused on invasion by non-native species as a principal cause (Castro et al 2007;Hoagstrom et al 2007;McKinney & La Sorte 2007;Magee et al 2008). While non-native species can cause large losses of native species in some circumstances (Maskell et al 2006a), national surveys accord with the results of this study in showing that non-natives are minor components of many British plant communities (Maskell et al 2006b).…”
Section: Discussionsupporting
confidence: 76%
“…In many cases, a single individual was collected, but in some waters several adults were caught and at times juveniles were present. Hoagstrom et al (2007) reported rudd in the Big Sioux River drainage in eastern South Dakota and the Cheyenne River drainage in western South Dakota.…”
Section: Introductionmentioning
confidence: 99%
“…Hybridization between rudd and golden shiners is possible in South Dakota, as golden shiners are present in most South Dakota river drainages (Hoagstrom et al 2007), but natural hybridization has not been documented.…”
Section: Introductionmentioning
confidence: 99%
“…Smallmouth bass are native to the northeastern corner of the state (Hoagstrom et al 2007) but were introduced into the Missouri River reservoirs beginning in the early 1980s to provide new angling opportunities (Milewski and Willis 1990;Berry and Young 2004). Some South Dakota walleye anglers believe that smallmouth bass are consuming young walleyes and reducing the abundance, growth, and condition of walleyes through competition for food (Brian G. Blackwell and John P. Lott, South Dakota Department of Game, Fish and Parks [SDGFP], personal communication).…”
mentioning
confidence: 99%
“…In South Dakota, walleyes Sander vitreus are native to the Missouri River reservoirs (Hoagstrom et al 2007) and are the most popular fish among anglers (Gigliotti 2007). Smallmouth bass are native to the northeastern corner of the state (Hoagstrom et al 2007) but were introduced into the Missouri River reservoirs beginning in the early 1980s to provide new angling opportunities (Milewski and Willis 1990;Berry and Young 2004).…”
mentioning
confidence: 99%